1995
DOI: 10.1091/mbc.6.5.611
|View full text |Cite
|
Sign up to set email alerts
|

The majority of yeast UPF1 co-localizes with polyribosomes in the cytoplasm.

Abstract: In Saccharomyces cerevisiae the UPF1 protein is required for nonsense-mediated mRNA decay, the accelerated turnover of mRNAs containing a nonsense mutation. Several lines of evidence suggest that translation plays an important role in the mechanism of nonsense mRNA decay, including a previous report that nonsense mRNAs assemble in polyribosomes. In this study we show that UPF1 and ribosomal protein L1 co-localize in the cytoplasm and that UPF1 co-sediments with polyribosomes. To detect UPF1, three copies of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
124
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(130 citation statements)
references
References 38 publications
5
124
1
Order By: Relevance
“…5 shows Qsr1p detected by fluorescein staining, and the center panel shows the L3 protein detected by Texas Red staining. The two proteins clearly colocalize, as indicated by spots that have been labeled with arrows to point out double labeling by both antibodies, and their staining patterns agree with previously published staining patterns for yeast ribosomal proteins (31,32).…”
Section: Colocalization Of Qsr1p and L3 By Indirectsupporting
confidence: 87%
“…5 shows Qsr1p detected by fluorescein staining, and the center panel shows the L3 protein detected by Texas Red staining. The two proteins clearly colocalize, as indicated by spots that have been labeled with arrows to point out double labeling by both antibodies, and their staining patterns agree with previously published staining patterns for yeast ribosomal proteins (31,32).…”
Section: Colocalization Of Qsr1p and L3 By Indirectsupporting
confidence: 87%
“…However, it is unclear whether some of the functions of Upf1 in fission yeast can be performed in the absence of Upf2 or Upf3, as described in other systems. 20,21,23 Addressing this question will require additional experiments.…”
Section: Methodsmentioning
confidence: 99%
“…There is also evidence that Upf1 and other components of NMD can play important functions in the cell independently of their role in the NMD process. [20][21][22][23][24] In fact, many targets of NMD factors do not have PTCs. 8,25 The fission yeast Schizosaccharomyces pombe contains Upf1 and Upf2 proteins, although the NMD mechanism is somehow different from mammals.…”
Section: Introductionmentioning
confidence: 99%
“…In yeast, nonsense-mediated mRNA decay (NMD), the degradation of mRNAs containing a premature translation termination codon, occurs by deadenylationindependent decapping followed by 59 r 39 exoribonucleolytic decay (Decker & Parker, 1993, 1994Muhlrad & Parker, 1994;Muhlrad et al+, 1994Muhlrad et al+, , 1995+ Two major steps of this turnover pathway are catalyzed by the products of DCP1 (Beelman et al+, 1996;LaGrandeur & Parker, 1998;Stevens, 1988) and XRN1 (Hsu & Stevens, 1993), and regulated by the product of UPF1 (Leeds et al+, 1991(Leeds et al+, , 1992Peltz et al+, 1993a;Weng et al+, 1996;Czaplinski et al+, 1998; He F & Jacobson A, in prep+; Maderazo A, He F, Mangus D, Jacobson A, in prep+)+ Deletion or mutation of UPF1 results in the stabilization and accumulation of nonsense-containing mRNAs without a concurrent increase in the abundance or stability of wild-type transcripts (Leeds et al+, 1992;He et al+, 1993;Czaplinski et al+, 1995)+ A twohybrid screen for UPF1 interactors identified six genes that passed genetic tests for specificity and thus encoded potential Upf1p-interacting proteins (He & Jacobson, 1995)+ Two of the genes identified in this screen, NMD2/UPF2 and DBP2, have been characterized further and shown to be additional components of the nonsense-mediated mRNA decay pathway (He & Jacobson, 1995;Cui et al+, 1995; Bond A, He F, Mangus D, Jacobson A, in prep+)+ A subsequent two-hybrid screen with NMD2, and an independent genetic screen, identified the UPF3 gene, which, when disrupted, also leads to selective stabilization of nonsense-containing mRNAs (Lee & Culbertson, 1995;He et al+, 1997)+ Further studies of the respective gene products have revealed that Upf1p, Nmd2p, and Upf3p either interact sequentially or function as a complex to regulate translation termination and promote mRNA decay (He et al+, 1997;Czaplinski et al+, 1998)+ Consistent with these roles, all three proteins have been shown to colocalize with polyribosomes and 80S ribosomes (Peltz et al+, 1993b;Atkin et al+, 1995Atkin et al+, , 1997Mangus & Jacobson, 1999)+ However, several different experimental approaches have failed to demonstrate an association betw...…”
Section: Introductionmentioning
confidence: 98%